Tracking Cairns: Biologging Improves the Use of Seabirds as Sentinels of the Sea - Brisson-Curadeau, Emile; Patterson, Allison; Whelan, Shannon; Lazarus, Thomas; Elliott, Kyle H. (Frontiers in Marine Science, 2017)
In 1987, David Cairns proposed that a gradient of colony-based measures on seabirds could be used to assess food supply in the ocean. Measures closely tied to the ocean, such as foraging trip duration, would be sensitive to small declines in food supply while measures more closely tied with the nest site, such as reproductive success, would be sensitive to large declines in food supply. The continual refinement of tracking devices holds the potential to clearly link variables measured via seabirds to food supply, possibly extending Cairns' hypothesis. Here, we review the various tests of Cairns' hypothesis, and demonstrate that those tests have had variable success, partly because of the complex and nonlinear relationships between food supply and colony-based measures. We summarize the metrics available from biologgers and argue that such devices can provide a more direct proxy of food supply. We conclude that Cairns' hypothesis can be extended to biologger-derived parameters and that seabird behavior can be used as an early warning signal for declining food supply.